Overweight and obesity and the demand for primary physician care - Nabanita Datta Gupta; Jane Greve (Institute for the Study of Labor (IZA), 2009)
The standard economic model for the demand for health care predicts that unhealthy behaviour such as being overweight or obese should increase the demand for medical care, particularly as clinical studies link obesity to a number of serious diseases. In this paper, we investigate whether overweight or obese individuals demand more medical care than normal weight individuals by estimating a finite mixture model which splits the population into frequent and non-frequent users of primary physician (GP) services according to the individual's latent health status. Based on a sample of wage-earners aged 25-60 years drawn from the National Health Interview (NHI) survey 2000 and merged to Danish register data, we compare differences in the impact of being overweight and obese relative to being normal weight on the demand for primary physician care. Estimated bodyweight effects vary across latent classes and show that being obese or overweight does not increase the demand for primary physician care among infrequent users but does so among frequent users.
Keywords: I12; I18; 330; Overweight; obesity; demand for primary physician care; Ärzte; Gesundheitsversorgung; Nachfrage; Gesundheitsrisiko; Dänemark